Compound type-dual blood supply to Gallbladder revealed during Laproscopic Cholecystectomy - Abdul Majeed; Mohammad Kamran Ch; Mohmmad Zakir; Tayyab Abbas (Aziz Fatimah Medical and Dental College, 2022)
SUMMARY During the laparoscopic cholecystectomy, a rare variation was found in a female patient. There was a large vessel exiting from liver parenchyma to gall bladder directly. It was pulsating; so was an unusual artery. The cystic artery was present properly at its usual anatomical site in Callot's triangle. The knowledge of these vascular variations is very significant in surgical interventions involving the biliary tree. It is of key importance for laparoscopic surgeons to know like this vascular variation to avoid catastrophic bleeding. The report emphasizes the vascular variation and the anomalous vessel to accomplish safe and uneventful hepatobiliary surgeri